Oral potentially malignant disorders: advice on management in primary care - Eccles Katherine; Carey Barbara; Cook Richard; Escudier Michael; Diniz-Freitas Marcio; Limeres-Posse Jacobo; Monteiro Luis; Silva Luis; Fricain Jean-Cristophe; Catros Sylvain; Lodi Giovanni; Lombardi Niccolò; et al. (EDP Sciences, 2022)
Introduction: The diagnosis of and risks associated with oral potentially malignant disorders (OPMD) have been widely reported, but little has been published on the management of OPMDs in a primary dental care setting. Hospital services face ongoing pressures due to long-term follow-up, with a need for surveillance to be jointly undertaken with primary dental care clinicians. In a primary care setting, identification and surveillance of OPMDs can be challenging as no universal guidance exists on recommended recall intervals. Corpus: In this article, an update on OPMDs is provided and, based on the practices of six Oral Medicine units in Europe (London (United Kingdom), Milan (Italy), Bordeaux (France), Porto (Portugal), Zagreb (Croatia) and Santiago de Compostela (Spain)), aiming to provide guidance on monitoring in a primary care setting in Europe. Conclusion: Oral medicine clinicians can provide guidance to general dental practitioners (GDPs) on recommended recall intervals. It is important that they feel confident in monitoring these conditions and, when concerned, to arrange referral to a hospital or appropriate specialist. GDPs should document descriptions of lesions and, if possible, take clinical photographs. Patients should be counselled on modifiable lifestyle factors and directed to oral medicine society websites to access patient information leaflets.